Transforming Waste Management in Rural Indonesia: Mentransformasi Pengelolaan Sampah di Pedesaan Indonesia - Mustafia, Ainun; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of the Sruni Village Government in waste management in Gedangan District. Despite efforts to improve waste management, challenges persist due to a lack of community understanding. The government has introduced facilities like a waste bank to reduce careless waste disposal. Using a qualitative descriptive method with purposive sampling, the research identifies four roles: stabilizer (implementing environmental programs), innovator (lacking in providing training), modernizer (establishing a waste bank), and pioneer (promoting independent waste sorting). Key challenges include community reluctance to segregate waste and inadequate waste collection facilities. The study underscores the need for better education and infrastructure to enhance waste management practices. Highlights: Government Roles: Stabilizer, innovator, modernizer, and pioneer in waste management. Challenges: Community reluctance and inadequate waste facilities. Solutions: Enhanced education and infrastructure for better waste management. Keywords: Waste management, Village government, Community engagement, Environmental policy, Sruni Village